Halal authentication of animal-derived fatty acids using FTIR-ATR spectroscopy and the principal component analysis approach - Nazri, Muhammad Zulhelmi; Abdul Latiff, Norliza; Abd Rashid, Siti Nor Azlina; Ab Malik, Salimah; A Karim, Hajar Aminah; Abdullah Sani, Muhamad Shirwan; Abang Zaidel, Dayang Norulfairuz; Basar, Norazah (Innovation Centre in Agritechnology for Advanced Bioprocessing (ICA), UTM, 2024)
Halal is a term coined in Arabic that describes any goods that, in accordance with Islamic law, that Muslims are permitted to consume. In the recent year, animal fats and vegetable oils have been considered as economic sources for food and oleochemical and pharmaceutical industries. The adulteration of fats and oils has been widespread in the food industry, involving the replacement of higher value products with lower grade, cheaper and more readily substitutes. The authenticity of fats and oils has been extensively investigated because they can easily be adulterated due to economic purposes. Mixing of animal fats with vegetable sources is a cause of concern for certain groups of consumers due to religious obligations and health complications [1]. The IR spectroscopy has drawn interest in the analytical community for use in the quantitative measuring of fats and oils. Due to IR is a vibrational type of spectroscopy and offers quick evaluation while being cost-effective, it is an excellent analytical approach for analyzing food and pharmaceutical products. Hitherto, the objective of this study is to evaluate the efficiency of FTIR-ATR and MVDA for halal authentication of animal fatty acids which might be broadly utilized in various industries including food production, cosmetics and pharmaceuticals. The important outcome of this FTIR-ATR spectroscopy effectiveness blended with MVDA techniques in differentiating among halal and non-halal animal fatty acids. The dried of lard and mutton oils FTIR spectra were obtained from INHART, IIUM through freeze dried method and were used directly. The fresh chicken, beef and pork were cut into smaller pieces using commercialcutter by 1 cm ⋅ 1 cm cube and were put into a vacuum drying oven and dried at 80 °C of temperature, 0.32 bar of pressure for 24h. The dried meats were collected and stored in the freezer. In the fat extraction procedure, 20 g of the dried meats were weighed and grinded as fine powder using a commercial blender before being put into cellulose extraction thimble. The extraction process was donein 6h using petroleum ether as the solvent. The obtained extracts were mixed with a spoonful of MgSO4 as to remove water, filtered through Whatman 125 mm diameter of filter paper, which then, later evaporated using a rotary evaporator, as the resultant oil were stored in glass vials. The Thermo Scientific Nicolet iS5 spectrophotometer model was used in the measurements. The ATR accessory equipped with diamond cell was used. All spectra were recorded within a range of 4000 – 650 cm-1 with4 cm-1 resolution and 32 scans. The spectra were converted into CVS format, imported to the dataset table in XLSTAT 2024 version software and the dataset was analysed accordingly for adequacy for thePCA analysis. All the FTIR-ATR spectra of functional and fingerprint’s spectra specifically of oil samples from dried meats and palm oil standard were measured at the wavenumber ranging from 4000to 650 cm-1 , respectively. The stretching vibration of -CH, CH2 and CH3 from aromatic and alkene could be observed at a peak of 3000 cm-1 whereas the stretching vibration of –CH, CH2 and CH3 from aliphatic alkane was found at peaks of ~2900 – 2800 cm-1 . It is observed that all the oils samples of animal/plant origin have a sharp and intense peak at the carbonyl (C=O) region of ~1700 cm-1 . The absorption bandat ~1400 cm-1 was correlated to the stretching vibration of C=C. The absorption bands at 1100 – 1000 cm-1 arise from the vibration of C–O stretching. In addition, vibrations at 1200 – 700 cm-1 were associated with bending vibrations of –CH, CH2 and CH3 fatty acid aliphatic backbone. Figure 1 showsthe outcomes of the PCA resultsfrom the FTIR-ATR wavenumber of 4000 – 650 cm-1 of all the animalsand palm oils samples. Moreover, before the PCA can proceed, all the FTIR-ATR spectra were subjected towards KMO test using the XLSTAT software for data adequacy and eligible for further analysis so that it must meet the requirement of KMO greater than 0.5. It is noted that the outcome of the KMO test of the FTIR-ATR spectra for the wavenumber of 4000 – 650 cm-1 is within the range of 0.757 – 0.888 meaning that all the spectra data is considered agreeably good. All the score plot of PCAshows distinct grouping of the animals and palm oil samples, respectively. Noteworthy, the lard showeda cluster grouping among the oils, and it is negatively correlated due to the opposite direction among all the samples. Visualising the PCA using the entire spectra in this complex due to the high number ofvariables as PCA cannot always solve multicollinearity-related problems with parameter estimation bymulticollinearity [2].